The Measurement of Technology Acceptance for Information Services in ‘ABC’ University Library Using Technology Acceptance Model - Eka Wahyu Hidayat; Husni Mubarok; Hilman Abdul Rahman (School of Industrial and System Engineering, Telkom University, 2020)
An adoption of technology always produces two reactions, namely acceptance or rejection. Senayan librarymanagement system is a library management system that is able to organize, organize, provide services,that finally producing an information that can help managers and library members. This study aims todetermine the extent to which technology in information services at the ‘ABC’ Library is received and toexamine the relationship of factors that influence the acceptance and use of these technologies by using theTAM (Technology Acceptance Model). Assessment is generated from primary data in the form ofquestionnaires distributed to 379 respondents. The veripative statistical analysis method in this study usesSEM (Structural Equation Model) with the software used is Amos 24. Based on the results of the research,PEOU has a positive effect on PU because the P value (0.013) <0.05, PEOU has no positive effect onBITU because P value (0.660)> 0.05, PU has a positive effect on BITU because P value (0.000) <0.05, andBITU has a positive effect on AU because the value of P (0.003) <0.05.